BIMA CULTURAL ETHNOMATHEMATICS AS A FOUNDATION FOR CONTEXTUAL MATHEMATICS LEARNING IN ELEMENTARY SCHOOLS - Azra Fauzi; I Wayan Lasmawan; Desak Putu Parmiti (Jurnal Cakrawala Pendas, 2026)
This study explores the mathematical concepts embedded in the cultural practices of the Bima community and examines their potential integration into elementary school mathematics learning. Using a qualitative exploratory approach, data were collected through field observations, in-depth interviews, and documentation of key cultural artefacts, particularly Uma Lengge (traditional stilt house) and Tembe Nggoli (traditional woven cloth). The findings reveal that both artefacts contain rich mathematical elements relevant to the elementary school curriculum, including geometry, measurement, proportional reasoning, numerical patterns, and symmetry. The architectural structure of Uma Lengge demonstrates applications of two- and three-dimensional shapes, balance, and non-standard measurement, while the motif patterns and weaving processes of Tembe Nggoli reflect concepts of repetition, arithmetic sequences, geometric shapes, and reflective symmetry. These cultural structures naturally embody mathematical reasoning developed through community practices. The integration of these artefacts into contextual learning promotes concrete understanding, strengthens students’ spatial reasoning, and enhances cultural literacy. The study also identifies challenges related to limited culturally grounded learning resources, insufficient teacher readiness, and lack of school policy support. Overall, the findings affirm that Bima ethnomathematics provides a meaningful and culturally rooted pedagogical foundation for implementing contextual, humanistic, and locally responsive mathematics education in elementary schools. Future research is encouraged to expand this cultural-based mathematics framework by exploring additional Bima cultural artifacts and testing its effectiveness through classroom-based experimental or quasi-experimental studies.